Thermoformable high oxygen barrier multilayer EVOH/LDPE film/foam. Issue 30 (4th February 2020) - Souza, Claudio; Feng, Jingxing; Olah, Andrew; Wnek, Gary; Baer, Eric
ABSTRACT: The effect of the number of layers on oxygen transmission and thermoformability of novel multilayer film/foam materials was investigated. Ethylene‐vinyl alcohol copolymer/low‐density polyethylene multilayered film/foam composites having 16, 32, and 64 alternating layers were developed using continuous multilayer coextrusion process, and the morphology, density, oxygen transmission, and mechanical properties of the as‐extruded film/foams were characterized. Tensile properties of the film/foams at elevated temperatures were used to optimize thermoforming conditions. Uniaxial orientation was discovered as an efficient approach to evaluate the potential for thermoforming. Oxygen transmission showed a strong correlation with the thickness reduction which could be used as an indicator for barrier properties of the packaging materials. Film/foam materials with 32 layers demonstrated optimum performance with low oxygen transmission along with high drawing capability. © 2020 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48903. Abstract : Cross‐section morphology of a coextruded 64 layer, 50/50, EVOH/LDPE film foam composition.